IMPLEMENTASI PROGRAM KESEHATAN REPRODUKSI REMAJA PADA SEKOLAH MENENGAH ATAS DI PROVINSI LAMPUNG: TANTANGAN DAN PELUANG - Listiansyah, Muhammad Alif; Caturiani, Susana Indriyati; Atika, Dewie Brima (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
Adolescent reproductive health is a health condition that concerns reproductive organ health issues whose readiness begins in adolescence. With the changes when entering adolescence, there needs to be supervision and guidance carried out by all levels, starting from the family at home and at school in order to protect teenagers from deviant behavior (free sex) and early marriage. The adolescent reproductive health program has been implemented in all districts/cities in Lampung Province. However, the number of cases of early marriage in Lampung Province can still be said to be high. Therefore, the adolescent reproductive health program is considered to be still not optimal in its implementation. This research aims to analyze the implementation of adolescent reproductive health programs in high schools in Lampung Province and identify supporting factors and obstacles faced in the process of implementing adolescent reproductive health programs in schools in the Districts/Cities of Lampung Province. The research method used is a qualitative approach with data collection techniques of observation, interviews and documentation. The results of research using Jones (1996) program implementation model including organization, interpretation and implementation show that the implementation of adolescent reproductive health programs in high schools in Lampung Province is still not optimal. Some of the obstacles faced are poor coordination between agencies, different student understanding and the absence of follow-up activities.